Pengaruh Ukuran Perusahaan, Profitabilitas dan Solvabilitas terhadap Nilai Perusahaan pada Perusahaan Manufaktur Subsektor Makanan dan Minuman di Bursa Efek Indonesia Tahun 2019-2021 - Patabang, Lewi; Fitriana, Rahmawati; Uswatuna Ulya (Politeknik Negeri Samarinda, 2024)
This study aims to determine the influence of accounting information systems, work experience, work environment and work motivation on employee performance at PT Bank Rakyat Indonesia (Persero) Tbk Branch Office 1 Samarinda. This study writing uses a quantitative approach using primary data through filling out questionnaires. The respondents at this writing are employees of PT Bank Rakyat Indonesia (Persero) Tbk. Branch Office 1 Samarinda operational part of the back office division. The Independent Variables used in this writing are accounting information systems, work experience, work motivation, and work environment. While the dependent variable in writing is employee performance. At this writing, the analysis tool used is multiple linear regression with the help of Statiscal Product and Services Solutions (SPSS) Version 22 software. Based on the results of the study, it was obtained that the Accounting Information System, work experience, work motivation and work environment simultaneously have a positive and significant influence on employee performance.